2020
DOI: 10.1007/s42729-020-00290-2
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Nitrogen Fixation by Mungbean Genotypes in Different Soil Textures Using 15N Natural Abundance Method

Abstract: Ensuring food and nutritional security in light of high climate variability and a rapidly growing population remains a challenge. Mungbean (Vigna radiata (L.) Wilczek) is a short duration, drought-tolerant, and ureide-exporting legume crop capable of symbiotic atmospheric nitrogen fixation. Estimates of biological N 2 fixation by mungbean in different soil textures have not been extensively studied. We conducted this study to evaluate plant growth and N 2 fixation of five mungbean genotypes (Berken, 8735, IC 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…The balance between stover removed to carbon returned to the system has to be considered to address economic concerns regarding short-term increases in nutrient removal rates and replacement costs (Battaglia, Groover, et al, 2018) for crop yield limiting nutrients such as N and P (Adeyemi et al, 2020;Adnan et al, 2020;Diatta et al, 2020;Ketterings & Czymmek, 2007). Blanco-Canqui and Lal (2009) found that only complete stover removal decreased N content in the soil, but this response was largely affected by soil texture.…”
Section: Crop Residue Management Effects On Nutrient Balances Ph Amentioning
confidence: 99%
“…The balance between stover removed to carbon returned to the system has to be considered to address economic concerns regarding short-term increases in nutrient removal rates and replacement costs (Battaglia, Groover, et al, 2018) for crop yield limiting nutrients such as N and P (Adeyemi et al, 2020;Adnan et al, 2020;Diatta et al, 2020;Ketterings & Czymmek, 2007). Blanco-Canqui and Lal (2009) found that only complete stover removal decreased N content in the soil, but this response was largely affected by soil texture.…”
Section: Crop Residue Management Effects On Nutrient Balances Ph Amentioning
confidence: 99%
“…For example, the global production of synthetic fertilizers amounted to 188.2 Mt in 2019 ( Figure 1 ) [ 4 ], while the current application of pesticides is about 4 Mt in agricultural fields [ 5 ]. It is expected that this amount of agrochemicals will be increased in the near future to an amount that could feed 9.6 billion people by 2050 [ 6 , 7 , 8 ]. Synthetic chemical fertilizers are used for the optimal growth and productivity of crops, but, at present, adopted agricultural practices have not been particularly successful to simultaneously enhance plant nutrient uptake, nutrient use efficiency (NUE), and crop productivity [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the long term, this intensive application of synthetic fertilizers can result in severe environmental risks such as air pollution, soil degradation, water eutrophication, and groundwater pollution [ 8 , 14 , 15 ]. Furthermore, the over-application of synthetic fertilizers increases the cost of their production and decreases the profit margin of farmers [ 7 , 8 ]. Low NUE values [ 16 ] and increased environmental risks [ 15 ] related to the use of more synthetic fertilizers has been a long-term limitation to achieve sustainability in agriculture [ 7 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations